The Use of Social Network Sites as an E-Recruitment Tool - Melanthiou, Yioula; Pavlou, Fotis; Constantinou, Eleni (My University, 2015)
The purpose of this article is to present an initial exploratory investigation on e-recruiting and the role of social network sites (hereafter SNSs) during the process. Particularly, the aim is to identify if companies use social media during their recruitment processes to attract and screen applicants. Three critical elements guided the research: the use of social media to attract and screen applicants; the legal implication of e-recruitment and social network screening; and the possibility of using e-recruitment as the main hiring strategy. Beyond the information generated through the literature review, primary data were collected from Cypriot organizations. The findings of this research endeavor indicate that the online recruitment method has a lot of benefits but also pitfalls of which recruiters should be aware. Furthermore, it seems that the contemporary practice of employee screening through social media can highly affect the hiring decision and legal implications are likely to arise with the wrong use of information. On the contrary, a well-designed system and strategic utilization of available information about potential candidates may significantly assist the recruitment of employees with the most suitable skills and competencies.
Keywords: social media; social networking; e-recruitment; employee screening; employee selection; internet; legal issues; recruitment